Exploring the Grounds for the Study of the Identity of Indigenous English Language Teachers in Colombia (GIST – Education and Learning Research Journal, 2020)
This article addresses the invisibilization of the existence of indigenous teachers in the Colombian ELT (English language teaching) field. Their existence, which is admittedly a phenomenon that lacks quantitative saliency, offers opportunities to reflect on the epistemological asymmetries that traditionally have linked the Colombian ELT field to an instrumental mainstream bilingualism, often ignoring the conditions of linguistic and cultural diversity in the country. Besides, there is an exploration of how the study of indigenous teachers’ identities might contribute to the re-signification of pedagogy; this paper elaborates on the idea that scholars in the Colombian ELT have already built some horizons of understanding between the ELT and the diversities and epistemic privileges of Colombian indigeneity. The article is part of an ongoing research on the identities of indigenous teachers in the Colombian ELT being carried out within the Interinstitutional Ph.D. in Education at Universidad Distrital Francisco José de Caldas, Bogotá
Keywords: Indigenous English language teachers; teacher identities; decolonial thought; cultural diversity; linguistic diversity